2022
DOI: 10.1126/sciadv.abo4250
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autoimmune disease progression by Pik3ip1 through metabolic reprogramming in T cells and therapeutic implications

Abstract: Metabolic alterations could profoundly affect immune functions and influence the progression and outcome of autoimmune diseases. However, the detailed mechanisms and their therapeutic potential remain to be defined. Here, we show that phosphatidylinositide 3-kinase interacting protein 1 (Pik3ip1), a newly identified negative immune regulator, is notably down-regulated in several major autoimmune diseases through a previously unidentified mechanism mediated by interleukin-21/p38 mitogen-activated protein kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…PIK3IP1 is a recently discovered negative regulator of PI3K, which can bind p110 and prevent its activation by p85, thereby down-regulating PI3K signaling to inhibit tumor growth [ 36 , 37 ]. Recent studies suggest that PIK3IP1 may act as a tumor suppressor to regulate tumor cell function [ 37 ] and anti-tumor immune activity [ 38 , 39 ]. In addition, PIK3IP1 is highly expressed in PI3Kα inhibitor-sensitive gastric cancer cells and can be used as a marker to detect the anti-cancer activity of PI3Kα inhibitor [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…PIK3IP1 is a recently discovered negative regulator of PI3K, which can bind p110 and prevent its activation by p85, thereby down-regulating PI3K signaling to inhibit tumor growth [ 36 , 37 ]. Recent studies suggest that PIK3IP1 may act as a tumor suppressor to regulate tumor cell function [ 37 ] and anti-tumor immune activity [ 38 , 39 ]. In addition, PIK3IP1 is highly expressed in PI3Kα inhibitor-sensitive gastric cancer cells and can be used as a marker to detect the anti-cancer activity of PI3Kα inhibitor [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of autoimmune diseases, PIK3IP1 is considered a key regulatory factor. This signaling plays a crucial role in the activation and regulation of immune cells, directly impacting their proliferation, differentiation, and activation state [ 23 ]. Research has also shown that by modulating the activity of the PI3K signaling pathway, PIK3IP1 affects biological processes such as proliferation, survival, and apoptosis in myocardial cells.…”
Section: Discussionmentioning
confidence: 99%
“… 44 PIK3IP1 is an upstream inhibitor of phosphoinositide 3‐kinase (PI3K) signalling, a novel negative immune regulatory factor. 45 These genes may play a significant role in the development and treatment of DFU.…”
Section: Discussionmentioning
confidence: 99%
“…TSC22D3 is a well‐known glucocorticoid‐induced gene with anti‐inflammatory effects and is also involved in regulating the differentiation of helper T cells 44 . PIK3IP1 is an upstream inhibitor of phosphoinositide 3‐kinase (PI3K) signalling, a novel negative immune regulatory factor 45 . These genes may play a significant role in the development and treatment of DFU.…”
Section: Discussionmentioning
confidence: 99%